Influence of wind disturbances and nonlinearities of servo drive on the contour of stabilization of the flight of height of unmanned aerial vehicle - V. A. Malkin; I. V. Rozhkov; A. A. San’ko (Системный анализ и прикладная информатика)
The article discusses a mathematical model of wind, taking into account its stochastic component and wind of a steady direction, presents the results of a comparative analysis of the effect of wind parameters on the total wind velocity vector acting on unmanned aerial vehicles (UAV). The main non-line arities of the autopilot servo elements and their influence on the output signal are considered. The reaction of the contour of the UAV flight altitude stabilization to the wind is considered, taking into account the nonlinearity of the servo drive elements. Proved the need to take into account the wind in the synthesis of automatic control systems (ACS) and the contours of the angular stabilization of the drone at stages where the flight speed of the drone is less than 30 m / s.